Respuestas

  • Usuario de Brainly
2013-03-09T19:35:32+01:00

x+ 3...........2x - 1

---------- + ---------- = 4

.....2..............3

 

3(x+ 3) + 2(2x - 1)

-------------------------- = 4

.....6............

 

3x + 9  + 4x - 2 = 4.6

7x  + 7 = 24

7x = 24 - 7

x = 17/7

 

espero que te sirva, salu2!!!!

 

  • Usuario de Brainly
2013-03-09T19:40:13+01:00

Resolvamos :

 

  ( x+3)              ( 2x -1)

----------     +    -------------    =   4

      2                       3

 

MCM de (2 y 3 ) = 6

 

3*(x+3) + 2*(2x-1)

--------------------------  = 4

               6        

    ( 3x +9 +4x -2) = 6*(4)

       ( 7x +7) = 24

         7x = 24 -7

         7x =  17

            x = 17/7

 

Espero te sirva , un SaLuDo :)''